How Does Maybank Build Long-term Customer Relationships? - Telitha Naomi Santhanasamy; Wei Bin Teoh; Yee Wen Teoh; Thanighesh Jaya Kannan (Global Academia Publisher, 2022)
Instituted in 1960, Maybank’s now the greatest banks in Malaysia by the market value of its shares and total assets. Given that the banking system has become a relationship-driven business worldwide, customers are important as they drive a company's revenues. The main aim of this paper is to identify the determinants of Maybank's long-term relationship with its customers. This study identifies the relationship between the independent variables (relationship marketing, service quality, price of services, corporate image, perceived value and customer satisfaction) and the dependent variables (long-term relationships between Maybank and its customers). The data was collected from 150 Maybank customers through the online survey. This paper will explore the contribution relationship marketing, service quality, price of services, corporate image, perceived value and customer satisfaction has on Maybank’s long-term relationship with its customers and to better understand its correlations.